Microcirculatory effects of physostigmine on experimental burn edema - Hernekamp, Jochen-Frederick; Klein, Henriette; Schmidt, Karsten; Vogelpohl, Julian; Kneser, Ulrich; Kremer, Thomas (Journal of burn care & research, 2015)
Abstract. In order to further understand the role of the cholinergic anti-inflammatory pathway, the authors determined the effects of burn plasma from donor ra